Composition and Density of Peryphyton on the leaves Thalassia hemprichii and Cymodocea rotundata at Panjang Island, Jepara - Tarisa Sekar Ayuningrum; Munasik; Ita Riniatsih (Prospect Publishing, 2023)
Seagrass as a flowering plant (Angiosperms) that can live in the marine environment well. One type of seagrass whose presence is dominant in Indonesian waters is the species Thalassia hemprichii and Cymodocea rotundata. Periphyton is an organism that has a close relationship with seagrass and has a role in seagrass as an increase in primary productivity. The purpose of this study was to determine the genus composition and density of periphyton on seagrass leaves Thalassia hemprichii and Cymodocea rotundata on Panjang Island, Jepara. The method carried out is seagrass leaf field data collection using the purposive sampling method with squared line transects. Seagrass leaf samples were taken and periphyton identification observations were made in the laboratory and then data processing analysis. Periphyton results were obtained from 10 classes, 39 genera and 1 type of zooplankton. Seagrass leaf periphyton density in both species is highest in old leaves and lowest in medium seagrass leaves. The periphyton diversity index of two seagrass species belongs to the medium category, the uniformity index belongs to the high category, and the dominance index shows that no genus dominates. The index value can indicate that the waters in the environment are still in stable condition.